Genetic diversity of provitamin a cassava in Uganda - Esuma, W.; Rubaihayo, P.R.; Pariyo, A.; Kawuki, R.S.; Wanjala, Bramwel W.; Nzuki, I.; Harvey, Jagger J.W.; Baguma, Yona K. (Canadian Center of Science and Education, 2012)
Global efforts are being made towards developing provitamin A cassava (Manihot esculenta Cranz) varieties for sustainably addressing vitamin A malnutrition commonly noted in communities where cassava is a major staple. To elucidate the diversity in Uganda’s core collection of yellow root cassava germplasm, genetic variability was assessed for 64 yellow and white root cassava accessions including Ugandan landraces, and accessions introduced from the International Center for Tropical Agriculture (CIAT) and the International Institute of Tropical Agriculture (IITA). Phenotypic characterization was based on 12 morphological descriptors, total carotenoid content (TCC) and dry matter content (DMC). Variation of twenty six simple sequence repeat (SSR) markers was assessed and compared with morphological data. Total carotenoid content varied from 1.2 to 14.2 ?g/100 g and correlated negatively (R2 = -0.46) with dry matter content which ranged from 27.2 to 39.8 %. Genetic diversity was high in all accession groups with an average heterozygosity of 0.5583 ± 0.0182. Phenetic analyses using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and Principle Coordinate Analysis (PCoA) clustered the CIAT accessions into a distinct group, discriminating them from the landraces and IITA accessions. Based on the clustering pattern, it suffices to suggest limited gene flow between CIAT accessions and the landraces/IITA accessions which is an opportunity for broadening the genetic base through hybridization by exploiting the heterotic pool in the germplasm.